Predictors of Comorbid Depression in Osteoarthritis Patients at Tertiary Care Settings of Islamabad - Rehana Khadim, Dr; Muhammad Tahir Yusuf, Dr; Wajahat Hussain, Dr; Ijaz Ahmed Shah, DR; Zahid Ahmed Butt, Dr; Aysha Babar, Dr (University of Lahore, 2022)
Objective: To estimate the co-morbid depression in the patients of knee osteoarthritis at the tertiary care hospital settings of Rawalpindi/Islamabad. Study Design: Cross sectional Analytical study Methods: Data of four hundred and four patients (n=404; 307 females and 97 males) was collected. Patients were selected from the OPD of Rheumatology Units of two Tertiary Care Hospitals of Rawalpindi/Islamabad and were assessed for co-morbid depression using Urdu translated Depression scale (CES-D). Basic demographical data and some variables directly having an impact with depression were assessed. Results: Frequency of co-morbid depression in osteoarthritis patients was 27.7%, of which females were 19.8% and males were 7.9%. Old age, illiteracy, rural residence, employment status, joint family system, obesity, co-morbidity with osteoarthritis, duration of disease and inability in performing routine activities were the variables positively associated with the depression (p< 0.05). Conclusion: Depression is comparatively prevalent in the osteoarthritis patients in Pakistan. Medical practitioners and rheumatologists must be vigilant about this co-morbidity and identify depression timely for the better attributions to life of the patients.